Frequent isolation of extended-spectrum beta-lactamase-producing bacteria from fecal samples of individuals with severe motor and intellectual disabilities. Issue 3 (March 2018) - Takano, Chika; Seki, Mitsuko; Shiihara, Hiroaki; Komine-Aizawa, Shihoko; Kuroda, Kazumichi; Takahashi, Shori; Ushijima, Hiroshi; Hayakawa, Satoshi
Abstract: Extended-spectrum beta-lactamase (ESBL) producing bacteria spread worldwide and became major concern for antibiotic treatment. Although surveillance reports in general hospitals and long-term care facilities are increasing, their frequencies in individuals with severe motor and intellectual disabilities (SMID) are so far unknown. In this study, we examined the frequency of ESBL in stool samples collected from 146 asymptomatic SMID subjects hospitalized in a single institution. With their clinical information, we evaluated possible risk factors for ESBL colonization. From 146 fecal samples, ESBL-producing bacteria were isolated in 45 cases (31%). Drug sensitivity testing showed that 82% of the isolates were resistant to levofloxacin but were sensitive to tazobactam/piperacillin and cefmetazole. The most frequent genotype was CTX-M-9 detected in 36/45 (80%). A high degree of disability, antibiotic use within three months before sampling and post-tracheostomy were statistically significant risk factors. Tube feeding was also strongly correlated with ESBL colonization (p < 0.001) and associated with lower micro-organismic diversities. Our findings are the first to reveal a high prevalence of ESBL in the fecal samples of SMID individuals and suggest possible relationships between high degree disability, tube feeding and latest histories of antibiotic use.